Effect of epicuticular waxes of fruits on the photodegradation of fenthion - Cabras, P.; Angioni, A.; Garau, V. L.; Melis, M.; Pirisi, F. M.; Minelli, E. V. (Amer Chemical Soc, 1997)
After treatment lipophilic pesticides tend to diffuse by penetrating the epicuticular wax of fruits. In this way, solar radiation only acts on pesticide molecules after passing through the waxes. The effect of epicuticular waxes of three fruits (orange, nectarine, and olive) on the photodegradation of fenthion was studied. The waxes affected the photodegradation process of fenthion. The decay rate of fenthion increased in the presence of orange and nectarine waxes, while it decreased when olive wax was used. In all waxes, the transformation of fenthion produced mainly fenthion sulfoxide and low amounts of fenthion sulfone. In orange wax, 50% of the initial fenthion was transformed into unknown compounds. In nectarine wax, fenthion was degraded stoichiometrically into fenthion sulfoxide and fenthion sulfone. In olive wax, the photodegradation of fenthion yielded about 80% of fenthion sulfoxide.
Keywords: fenthion; photodegradation; fruits; wax